Miedo al otro: comunicación, poder y representación en una contemporaneidad sobresaltada (2002)
Based on data and information both Anthropology and Communication Science, we take up in this paper the question about the other different and generally or commonly excluded. From Anthropology, we Insist In the Invitation to assume the knowledge of alterity as a possibility and not as anomaly. In a violent and excluding context with all the risk derived from modernity. And from the Communication, we center our attention in the various devices and tools to configure presence and Insistence of other in world wherewhat is at stake is the capacity to give including dimension to public aspects.Considering what happened on September 11/01 in New York as maximum expression of irruption of Eastinto West, we touch upon such characters as terrorists and drug traffickers or drug lords who certainlychallenge the assumptions on which multiculturalism and interculture are based. In this context, mediaact is a representation producers, a role in which they show their classifying as stigmatizing power underthe appearance of technological neutral mediating.